Modifications of Rect-Spring to Enhance the Engagement of Ectopically Entrapped Molars with 2 Case Reports - Min Sun Song; Chung-Min Kang; Je Seon Song; Hyung-Jun Choi; Jaeho Lee; Seong-Oh Kim (MDPI AG, 2021)
The Rect-spring appliance, used for the management of ectopically erupting molars, shows weak retention on mesially tilted molars. We present three modifications of the appliance for better engagement and their advantages. We describe cases of two 7-year-old patients with ectopically erupting maxillary first molars with a 2.2 mm and 2.5 mm depth of entrapment, respectively. The modified Rect-spring (mRS) was inserted between the ectopically erupting first molar and adjacent primary second molar, and exerted a distalization force with an interproximal wedging effect at the same time. After 3 months, the ectopically erupting first molars were successfully brought into proper occlusion. No discomfort was reported. The mRS is suitable for various locking cases except for severely tilted molars without requiring any laboratory procedures. We suggest it as the first choice for unlocking the first molars.